Oral Tradition in Pantun of Langkat Malay Traditional Wedding Ceremony - Muhammad Natsir; Bakhrul Khair Amal; Supsiloani Supsiloani; Rita Suswati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The purpose of this study was to conduct the oral tradition in Pantun of Langkat Malay traditional wedding ceremony by using Sibarani’s theory. Oral Tradition itself is text, co-text, and context tradition. The method used in this paper was descriptive and qualitative. For collecting the data the researcher became an instrument by doing observation and unstructured interview. Analysis technique used which were transcribing, reading, comprehending, investigating, describing, and explaining. The findings of text showed theme in Pantun that uttered by telangkai contained gratitude, honor, tradition, persuasion, joke, hoping a kindness, signifying a peace, welcoming guest, enthusiastic, teasing which briefly supported by co-text and context. Co-text described paralinguistic, kinetic, proxemic, and material elements. Some context applied as follow; cultural context, social context, context of situation, and culturalcontext.